Testament - Heit, Stephanie (Disability Studies Quarterly, 2017)
As an empowering antidote to the psychiatric system, this piece repossesses and plays with medical establishment language. It indexes the drugs and treatments for bipolar disorder I’ve tried over the course of twenty years and multiple psychiatric hospitalizations. Initially written after a series of inpatient stays in my late 20’s, I recently revised "Testament" after another inpatient intensive period to include new treatment trials and psych unit jargon. An audio recording of "Testament" is available at http://hdl.handle.net/1811/79959